Kritik Istihsan Terhadap Konstruksi Faraid Amina Wadud - Rama, Faby Toriqir (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2018)
This paper is a bibliographical research on Amina Wadud’s thought about faraid with istihsan theory. The main problem is about the style of Amina Wadud’s thought which is considered by some people to be contrary to the building of the Shari’ah. The construction of Amina Wadud's thoughts on faraid is built on the foundations of hermeneutical analysis with a justice and gender equality approach. She focuses on the Qur’an in chapter al-Nisa’ verses 11 and 12. The author finds that although Amina Wadud used the hermeneutic approach and the principle of justice and gender equality, there is still much room for criticism when viewed from the perspective of istihsan . First, Amina Wadud does not write that Islamic law is in fact flexible, as evidenced by the takharruj mechanism which is essentially an istihsan product. Second, less exploration of the shari’s proposition. Amina Wadud has a remarkable rhetoric and depth of philosophy. But in the field of faraid discussion he narrows himself to the use of the Qur’an without considering any other propositions. Third, istihsan bi al-nas-one kind, istihsan-writer uses to fight her improper argument about the concept of naf’a which he introduced herself by referring to chapter al-Nisa’ verse 11. [Artikel ini adalah hasil penelitian pustaka analitis yang membahas konstruksi pemikiran Amina Wadud tentang faraid dengan teori istihsan. Permasalahan yang menjadi pokok bahasan adalah tentang corak pemikiran Amina Wadud yang dianggap sebagian orang bertentangan dengan bangunan syariat. Konstruksi pemikiran Amina Wadud tentang faraid dibangun melalui fondasi analisis hermeneutika dengan pendekatan keadilan dan kesetaraan gender. Fokus ayat alQur’an yang ia teliti berada pada Surat al-Nisa’ ayat 11 dan 12. Penulis menemukan bahwa meskipun Amina Wadud menggunakan pendekatan hermeneutik dan juga prinsip keadilan serta kesetaraan gender, ternyata masih terdapat banyak ruang kritik jika dilihat melalui perspektif istihsan. Pertama, Amina Wadud tidak menuliskan bahwa sebenarnya hukum kewarisan Islam itu fleksibel, terbukti dengan adanya mekanisme takharruj yang secara hakikat merupakan produk istihsan. Kedua ia, kurang mengeksplorasi dalil shar’i. Amina Wadud di satu sisi memiliki kemampuan retorika dan kedalaman filsafat yang luar biasa. Namun dalam pembahasan faraid ia mempersempit dirinya pada penggunaan al-Qur’an tanpa mempertimbangkan dalil yang lain. Ketiga, istihsan bi al-nas—salah satu jenis , istihsan—penulis gunakan untuk melawan argumennya yang tidak tepat tentang konsep naf’a yang diperkenalkannya sendiri dengan mengacu pada Surat al-Nisa’ ayat 11.]